Universiti Malaysia Pahang’s Digital Literacy Program for Preschool Children - Irene, Wei Kiong Ting (2018)
‘Ready or not, here we come’ for digital literacy because we live in a digital era with all information we need at the tip of our fingers. We find not only no more geographic boundaries, but also no fine lines between a user and a designer. Today, digital technology is synonym to human beings, regardless of their age and nationality, attributable to the advancements of human-computer-interaction technology. Digital devices have never been more user friendly than they are today. For example, the usability of smartphones is almost intuitive – even a child would be able to use it with ease. Thus, questions arise: -What does digital literacy mean to preschoolers?